UTILIZATION OF ACTIVATED CARBON FROM COCONUT SHELLS IN THE BLEACHING PROCESS OF CRUDE PALM OIL (CPO) - Novrizal, Yedil; Sari, Ratna; adriana, A (Jurnal Sains dan Teknologi Reaksi, 2024)
CPO (Crude Palm Oil) is the result of processed palm fruit in the form of crude oil so that it needs to be refined so that it can be used by consumers, one of the purification processes of CPO (Crude Palm Oil) is to use the bleaching process. The purpose of this study is to determine the effect of activated carbon size, temperature and bleaching process time on the crude palm oil (CPO) produced. This study used three independent variables, namely the size of activated carbon (120/150, 150/180 and 180/200) mesh and bleaching temperatures of 150oC, 160oC, 170oC and bleaching times of 50 minutes, 60 minutes and 70 minutes. The results showed that the higher the temperature and time in the bleaching process, the lower the level of free fatty acids in CPO both in the size of activated carbon (120/150, 150/180 and 180/200) mesh. In activated carbon, the ash content did not meet the SNI 06-3730-1995 standard while the moisture content met the standard. For CPO (Crude Palm Oil) after the bleaching process, the  best results were obtained at a particle size of 120/150 mesh with a temperature of 170oC and a time of 70 minutes. Keywords: Crude palm oil (CPO), activated carbon, and bleaching